Sizing agent for bulletproof material as well as preparation method and application of sizing agent

By combining dopamine hydrochloride, trimethylolamide hydrochloride and aqueous polyurethane adhesive, a modified sizing agent suitable for UHMWPE fiber is formed, which solves the problem of poor adhesion between fiber and resin and achieves high strength and high toughness and composite materials with good interface performance reduce production costs and reduce environmental pollution.

CN119121628AActive Publication Date: 2024-12-13NANTONG HENGSHANG NEW MATERIAL TECH CO LTD +1

Patent Information

Application Number
CN202411284314.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-13
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

The lack of sizing agents suitable for ultra-high molecular weight polyethylene fiber (UHMWPE) fibers in the prior art leads to poor adhesion between the fiber and the resin, and traditional sizing agents have problems with environmental protection and dispersion stability.

Method used

Dopamine hydrochloride and trimethylolamide hydrochloride are combined with aqueous polyurethane adhesive to form a modified sizing agent. It is uniformly distributed on the surface of UHMWPE fibers through simple stirring and dipping processes to form a stable physical network structure. Improve the interface compatibility and adhesion between fiber and resin.

Benefits of technology

The high strength, high toughness and good interface performance of UHMWPE fiber are achieved, which reduces production costs, and the components are non-toxic to the human body, have strong adaptability, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121628A_ABST
    Figure CN119121628A_ABST
Patent Text Reader

Abstract

The invention discloses a sizing agent for a bulletproof material as well as a preparation method and application of the sizing agent, and belongs to the field of functional materials. The sizing agent for the bulletproof material comprises the following components: an adhesive, dopamine hydrochloride and tris (hydroxymethyl) aminomethane hydrochloride, wherein the mass ratio of the adhesive to the dopamine hydrochloride to the tris (hydroxymethyl) aminomethane hydrochloride is (99.36 to 99.68) to (0.2 to 0.4) to (0.12 to 0.24). The sizing agent can be used for UHMWPE fibers and further used for bulletproof materials. The sizing agent prepared by the invention can be used for a waterborne polyurethane adhesive; and the preparation process is simple and suitable for industrial use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a sizing agent for bulletproof materials and a preparation method and application thereof, belonging to the field of functional materials. Background Art

[0002] Ballistic materials are key components in personal and vehicle protective equipment. They are usually made of multiple layers of high-performance fiber fabrics, such as aramid, ultra-high molecular weight polyethylene fibers, etc. These fiber materials are valued for their light weight, high strength and impact resistance. However, in order to make these fiber materials suitable for ballistic equipment, they need to undergo a specific sizing treatment to enhance their mechanical properties and impact resistance.

[0003] In the field of textile composite materials, optimizing the sizing process to improve the surface style, interface performance, mechanical properties and flame retardant properties of composite materials is a common optimization method in the industry. Therefore, it is necessary to prepare a modified sizing agent that can optimize the above properties to achieve the preparation of lightweight and high-strength fiber composite materials and improve the mechanical properties and impact resistance of composite materials in practical applications. Under ideal conditions, the modified sizing agent should meet the following requirements: ① Form a film on the surface of the fiber or fabric after padding; ② Improve the interface properties of the composite material; ③ Have a smaller particle size; ④ Good storage stability; ⑤ Low surface tension and good wettability.

[0004] The sizing agents used in conventional high-performance fibers mainly include modified PEEK, polyimide precursors, polyetherimide, etc., as well as solvent-based and emulsion-based sizing agents. High-performance UD laminates are often sizing with water-based adhesives, of which the most commonly used are polyurethane adhesives, and a small number are acrylic adhesives. Since the effect of acrylic adhesives during use is significantly affected by temperature and humidity, the material will crust and slag after sizing in winter, so it accounts for a small proportion in actual use. These sizing agents play an important role in the manufacturing process of high-performance fibers. They can form a functional organic polymer layer on the surface of high-performance fibers, optimize the wear resistance, bundling, and spreading properties of the fibers, improve the wettability and bonding ability with the matrix, and thus enhance the interfacial strength of the composite material.

[0005] However, these sizing agents also have some common problems during use, mainly including:

[0006] 1. Environmental issues

[0007] Sizing agents, especially traditional oil-soluble sizing agents, contain organic solvents, which are easy to volatilize, not only polluting the environment, but also affecting the health of workers. Therefore, the development of water-based, organic solvent-free sizing agents has become an important research direction in the industry.

[0008] 2. Bonding issues with fibers and resins

[0009] Since sizing agents require the use of a large amount of emulsifiers, which are essentially surfactants, they may make the fiber surface easily absorb moisture and affect the bonding between the fiber and the resin.

[0010] 3. Dispersion stability issues

[0011] Water-based sizing agents prepared by traditional methods such as stirring have problems such as large emulsion particle size, unevenness and instability, which will affect the performance of the sizing agent and the performance of the fiber.

[0012] UHMWPE fiber, also known as high-strength high-modulus polyethylene fiber, is one of the three major high-tech fibers in the world today (carbon fiber, aramid fiber and ultra-high molecular weight polyethylene fiber), and is also the toughest fiber in the world. The molecular weight of UHMWPE fiber is between 1 million and 5 million, which is dozens of times that of ordinary fibers, and has extremely excellent performance. The strength of UHMWPE fiber is 15 times that of steel, and 2 times higher than carbon fiber and aramid 1414 (Kevlar fiber). It plays an important role in bulletproof vests, high-performance composite materials, ropes, fisheries and other fields. However, there are currently few studies related to sizing agents for UHMWPE fibers, which may be related to its special molecular structure. The molecular structure of UHMWPE fiber is a linear polymer, composed of up to millions of ethylene molecules (—CH2-CH2—), without side chains. This linear molecular structure gives UHMWPE fiber excellent physical and chemical properties. Due to the neat and smooth structure of the fiber surface and the small number of active groups, the adhesion between the resin and the fiber is poor.

[0013] Therefore, the UHMWPE fiber sizing agent should have good dispersibility and stability to ensure that the sizing agent can be evenly and stably distributed on the UHMWPE fiber surface; it should have good interfacial compatibility to ensure that the sizing agent can effectively adhere to the fiber surface. Summary of the invention

[0014] [Technical issues]

[0015] Currently, no sizing agent has been found that can be used for UHMWPE fibers.

[0016] [Technical solution]

[0017] In order to solve the above problems, the present invention provides a sizing agent for bulletproof materials and a preparation method and application thereof. Specifically, the present invention uses dopamine hydrochloride and trishydroxymethylaminomethane hydrochloride to modify the adhesive to form a modified sizing agent, so that it can be used for UHMWPE fibers and then for bulletproof materials. The sizing agent prepared by the present invention can be used for water-based polyurethane adhesives; and the preparation process is simple and suitable for industrial use.

[0018] The first object of the present invention is to provide a sizing agent for bulletproof materials, the components of which are adhesive, dopamine hydrochloride and tris(hydroxymethyl)aminomethane hydrochloride; wherein the mass ratio of the adhesive, dopamine hydrochloride and tris(hydroxymethyl)aminomethane hydrochloride is 99.36-99.68:0.2-0.4:0.12-0.24.

[0019] In one embodiment of the present invention, the adhesive is a water-based polyurethane adhesive.

[0020] A second object of the present invention is to provide a method for preparing a sizing agent for a bullet-proof material, comprising the steps of:

[0021] The adhesive, dopamine hydrochloride and tris(hydroxymethyl)aminomethane hydrochloride) are uniformly mixed in a mass ratio of 99.36-99.68:0.2-0.4:0.12-0.24 to react to form a mixed solution; after the reaction is completed, the mixed solution is defoamed, filtered and packaged to obtain a sizing agent for bulletproof materials.

[0022] In one embodiment of the present invention, the reaction is carried out at room temperature and pressure with stirring at 220-300 rpm for 23-25 ​​hours.

[0023] In one embodiment of the present invention, the defoaming is performed by standing.

[0024] In one embodiment of the present invention, the filtration is performed using a 0.15-0.45 μm glass fiber filter membrane.

[0025] The third object of the present invention is to provide a UHMWPE fiber for bulletproof material, which uses the sizing agent for bulletproof material of the present invention.

[0026] A fourth object of the present invention is to provide a method for sizing UHMWPE fibers using a sizing agent for bulletproof materials, comprising the following steps:

[0027] The UHMWPE fiber is placed in a sizing agent for bulletproof material, impregnated and rolled, and dried to obtain the UHMWPE fiber for bulletproof material.

[0028] In one embodiment of the present invention, the padding is performed at room temperature and pressure, with two dips and two pads, and the padding ratio is 60-80%.

[0029] In one embodiment of the present invention, the drying is performed at 50-70° C. for more than 20 min.

[0030] A fifth object of the present invention is to provide a UHMWPE fiber composite material, which uses the sizing agent for ballistic-proof material or the UHMWPE fiber for ballistic-proof material described in the present invention.

[0031] A sixth object of the present invention is to use the sizing agent for bullet-proof materials or the UHMWPE fiber for bullet-proof materials of the present invention in the field of protective equipment or functional materials.

[0032] A seventh object of the present invention is to provide a method for improving the interfacial compatibility between resin and UHMWPE fiber, which uses the sizing agent for bullet-proof material of the present invention.

[0033] The eighth object of the present invention is to provide a method for improving the tensile properties of UHMWPE fibers, which uses the sizing agent for bulletproof materials described in the present invention.

[0034] [Beneficial Effects]

[0035] (1) The tris(hydroxymethyl)aminomethane hydrochloride added in the present invention plays a role in controlling the pH of the solution and maintaining the stability of the dopamine hydrochloride system.

[0036] (2) The components used in the present invention are non-toxic to the human body and have a high safety factor.

[0037] (3) The preparation process of the present invention is simple and easy to operate.

[0038] (4) The amount of sizing agent used in the present invention is reduced, thereby reducing production costs.

[0039] (5) The sizing agent of the present invention can be used for UHMWPE fibers and can significantly improve the performance of UHMWPE fibers.

[0040] (6) The sizing agent of the present invention has good water-based conditions and is easy to mix with water, thereby reducing environmental pollution.

[0041] (7) The present invention can realize the in-situ growth of unidirectional polydopamine, thereby improving the adhesion and durability of the sizing agent.

[0042] (8) The sizing agent of the present invention has strong adaptability and can be used to modify the molecular chains of polymers with different structures to optimize and improve their adhesion, mechanical and other properties.

[0043] (9) The sizing agent of the present invention can be used to manufacture UHMWPE fibers or fabrics into optimized composite materials with high strength and high toughness through simple stirring and padding processes.

[0044] (10) The catechol and amino functional groups in the dopamine molecules used in the present invention enable them to have good self-polymerization coating function. The dopamine molecules interact with the surface of the UHMWPE fiber through physical effects (such as van der Waals forces, hydrogen bonds, etc.), and form a stable physical network structure through π-π bond stacking. This physical network structure changes the microscopic morphology and chemical properties of the fiber surface, and because the dopamine molecule surface has abundant hydroxyl groups, the active groups on the fiber surface increase, and the compatibility of the fiber and the resin is improved, thereby achieving a comprehensive improvement in the fiber surface properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a SEM scanning electron microscope microscopic comparison diagram of Example 1 and Comparative Example 1 before and after sizing.

[0046] Figure 2 Schematic diagram of a sample of a microsphere debonding test on a sized UHMWPE tow prepared with the sizing agent of Example 1.

[0047] Figure 3 Schematic diagram of the debonding performance test sample of the UHMWPE filament bundle after sizing prepared by the sizing agent of Example 1; wherein (a) is a silicone mold with a reserved incision; (b) is a real picture of the TEBT sample; and (c) is a schematic diagram of the TFBT sample. DETAILED DESCRIPTION

[0048] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.

[0049] Test method:

[0050] 1. Mechanical properties test:

[0051] The tensile test of UHMWPE tow was carried out using QJ series microcomputer-controlled electronic universal testing machine.

[0052] Tensile test reference standard: GB / T 3362-2017 "Test method for tensile properties of carbon fiber multifilament". The main steps are as follows:

[0053] (1) Use the machine button to adjust the position of the chuck on the universal testing machine so that the chuck length is greater than the sample length of the tow sample.

[0054] (2) Place the reinforcing sheet at one end of the wire bundle vertically into the upper chuck of the testing machine, and rotate the knob above the chuck to gradually tighten the upper chuck to clamp one end of the reinforcing sheet.

[0055] (3) Adjust the distance between the chucks so that the reinforcing piece at the other end of the tow specimen can be placed in the lower chuck of the testing machine. After ensuring that the lower reinforcing piece and the lower chuck of the testing machine are level, tighten the lower chuck of the testing machine using the knob.

[0056] (4) After the reinforcing sheets at both ends of the tow are clamped by the chuck, the tow tensile test can be carried out. The loading rate of the testing machine is 20 mm / min, the chuck distance is 150 mm, and each sample is tested at least 5 times to take the average value.

[0057] 2. Contact angle test:

[0058] The hydrophilicity of the adhesive and the surface of PE woven fabric before and after modification was tested using a CA100B contact angle (water drop angle) meter.

[0059] Water contact angle test reference standard: GB / T 42694-2023 "Test and evaluation of anti-wetting properties of textile surfaces - Contact angle and rolling angle method".

[0060] The main steps are as follows:

[0061] (1) Adjust the liquid supply device so that it absorbs an appropriate amount of reagent. If there are bubbles at the injection head, they need to be discharged to ensure that there are no bubbles in the liquid supply device.

[0062] (2) Use a level to level the sample table, and fix the instrument debugging sample on the sample table with the test surface facing upward.

[0063] (3) Set the injection liquid volume to 5 and the injection head to be about 2 mm away from the surface of the test sample.

[0064] (4) Add (5 ± 1) μL of liquid to the surface of the instrument debugging sample, remove the injection head, and adjust the camera and sample stage to make the droplet image clear and of appropriate size. When the droplet is hemispherical or nearly spherical, the droplet diameter is about 1 / 3 of the image window length.

[0065] (5) Remove the instrument debugging sample, wipe the sample table to keep it dry, install the test sample, drip (5±1)uL on the sample surface, remove the injection head after the droplet, take a picture of the sample and the droplet on it when the contact time is 30s, use the measurement system to calculate the left and right contact angles of the droplet, and take the average of the two contact angles as the contact angle of the sample.

[0066] 3. Composite material interface performance test:

[0067] (1) Interface shear strength test

[0068] The interfacial shear strength between the fiber and the resin was tested by microsphere debonding experiment.

[0069] The main steps are as follows:

[0070] Preparation of microsphere debonding test samples: Take out the monofilaments from the UHMWPE fiber bundle and fix them at both ends of the double right-angle axis frame and give the monofilaments a certain pre-tension, and try to keep the pre-tension consistent. Mix the epoxy resin and polyetheramine curing agent evenly by mechanical stirring according to the weight ratio of 3:1, and then degas in a vacuum environment for 15 minutes to obtain a pure and bubble-free resin sample. Use a needle tip to transfer a small amount of resin droplets to the surface of the test fiber. Finally, the resin droplets are cured at 80°C for 2 hours. Finally, the microsphere debonding test is carried out on the YG163 electronic microsphere debonding tester.

[0071] (2) Interface bonding strength test

[0072] The TFBT experiment was used to evaluate the effect of modification on the interfacial bonding performance.

[0073] The main steps are as follows:

[0074] Preparation of TFBT experimental samples: The TFBT experiment requires stretching the fiber bundle under clamping to evaluate the bonding level between the fiber and the matrix. Considering that the resin matrix of the subsequent laminate is water-based polyurethane, hard polyurethane resin is selected as the raw material to prepare the TFBT sample. At room temperature, the fiber bundle is horizontally embedded in a silicone mold with a pre-reserved incision, and a small amount of resin liquid is pre-infiltrated into the UHMWPE fiber bundle. After curing for 1 hour, the resin is poured into the mold for curing and molding. The size of the prepared TFBT specimen is 100mm*20mm*4mm. Finally, the interface bonding strength test is carried out on a 3385H electronic universal testing machine.

[0075] 4. Ballistic Limit V of Laminated Composite Materials 50 test:

[0076] Refer to GA950-2019 Bulletproof Materials and Products V 50 Test Methods”;

[0077] The test uses a cylindrical wedge-shaped simulated fragment with a mass of (1.1±0.02) g as the launching projectile, and evaluates the ballistic limit V50 value of the bullet-proof composite plate with a size of 400mm×400mm.

[0078] The evaluation method is:

[0079] In the effective hit shooting, take the arithmetic mean of the bullet velocities of the six measuring points with opposite results and equal number and correct the calculation to get the V value of the sample. 50 value.

[0080] The raw materials used in the examples are:

[0081] Adhesive A: Water-based polyurethane adhesive, purchased from Covestro Polymer Co., Ltd., model U42;

[0082] Adhesive B: water-based polyurethane adhesive, purchased from Covestro Polymer Co., Ltd., model UXP 2643;

[0083] Dopamine hydrochloride: chemically pure 98%, purchased from Shanghai Myril Biochemical Technology Co., Ltd.;

[0084] Tris(hydroxymethyl)aminomethane hydrochloride: analytical grade 98.5%, purchased from Shanghai Myrrel Biochemical Technology Co., Ltd.;

[0085] UHMWPE tow: 1600D, purchased from Jiangsu Henghui Security Co., Ltd.

[0086] Example 1

[0087] A method for preparing a sizing agent for a bulletproof material comprises the following steps:

[0088] Adhesive A, dopamine hydrochloride, and tris(hydroxymethyl)aminomethane hydrochloride) were mixed in a mass ratio of 99.68:0.2:0.12, and stirred at 300 rpm for 24 hours at room temperature and pressure to form a mixed solution;

[0089] After the reaction is completed, the mixed solution is allowed to stand for defoaming until the foam on the surface of the solution disappears; then, impurities are removed by filtering with a 0.20 μm glass fiber filter membrane, and the mixture is packaged to obtain a sizing agent for bulletproof materials.

[0090] Example 2

[0091] A method for preparing a sizing agent for a bullet-proof material comprises the following steps:

[0092] Adhesive A, dopamine hydrochloride, and tris(hydroxymethyl)aminomethane hydrochloride) were mixed in a mass ratio of 99.52:0.3:0.18, and stirred at 300 rpm for 24 hours at room temperature and pressure to form a mixed solution;

[0093] After the reaction is completed, the mixed solution is allowed to stand for defoaming until the foam on the surface of the solution disappears; then, impurities are removed by filtering with a 0.20 μm glass fiber filter membrane, and the mixture is packaged to obtain a sizing agent for bulletproof materials.

[0094] Example 3

[0095] A method for preparing a sizing agent for a bulletproof material comprises the following steps:

[0096] Adhesive B, dopamine hydrochloride, and tris(hydroxymethyl)aminomethane hydrochloride) were mixed in a mass ratio of 99.68:0.2:0.12, and stirred at 300 rpm for 24 hours at room temperature and pressure to form a mixed solution;

[0097] After the reaction is completed, the mixed solution is allowed to stand for defoaming until the foam on the surface of the solution disappears; then, impurities are removed by filtering with a 0.20 μm glass fiber filter membrane, and the mixture is packaged to obtain a sizing agent for bulletproof materials.

[0098] Example 4

[0099] A method for preparing a sizing agent for a bullet-proof material comprises the following steps:

[0100] Adhesive B, dopamine hydrochloride, and tris(hydroxymethyl)aminomethane hydrochloride) were mixed in a mass ratio of 99.52:0.3:0.18, and stirred at 300 rpm for 24 hours at room temperature and pressure to form a mixed solution;

[0101] After the reaction is completed, the mixed solution is allowed to stand for defoaming until the foam on the surface of the solution disappears; then, impurities are removed by filtering with a 0.20 μm glass fiber filter membrane, and the mixture is packaged to obtain a sizing agent for bulletproof materials.

[0102] Example 5

[0103] The mass ratio of adhesive A, dopamine hydrochloride and tris(hydroxymethyl)aminomethane hydrochloride in Example 1 was adjusted to 99.36:0.4:0.24, and the other ratios were kept consistent with Example 1 to obtain a sizing agent for bulletproof material.

[0104] Comparative Example 1

[0105] Adhesive A was used directly as the sizing agent.

[0106] Comparative Example 2

[0107] Adhesive B is used directly as the sizing agent.

[0108] Comparative Example 3

[0109] The dopamine hydrochloride in Example 1 was adjusted to tannic acid, and the other parts were kept consistent with Example 1 to obtain a sizing agent for bulletproof material.

[0110] Comparative Example 4

[0111] The tris(hydroxymethyl)aminomethane hydrochloride) in Example 1 was adjusted to water, and the other conditions were kept consistent with Example 1 to obtain a sizing agent for bulletproof material.

[0112] Comparative Example 5

[0113] The tris(hydroxymethyl)aminomethane hydrochloride) in Example 1 was adjusted to an ammonia-ammonium chloride buffer solution, and the other aspects were kept consistent with Example 1 to obtain a sizing agent for bulletproof material.

[0114] Example 6

[0115] A method for sizing UHMWPE fibers using a sizing agent for bulletproof materials comprises the following steps:

[0116] The UHMWPE tow is dipped and rolled at room temperature and pressure using a sizing agent for bulletproof materials, with two dips and two rolls, and the roll-over rate is 65%; the tow is dried in an oven at 60° C. for 30 minutes to obtain the sized UHMWPE tow.

[0117] The obtained UHMWPE tow was subjected to mechanical property test, and the contact angle test was performed on the plain weave fabric woven from the UHMWPE tow. The test results are as follows:

[0118] It can be seen from Table 1 that the mechanical properties of the sizing agent treated filaments prepared in Examples 1-5 are significantly better than those of the corresponding unmodified adhesives, and their tensile strength and elongation at break are increased; the hydrophilicity of the sizing agent films prepared in Examples 1-5 increases, indicating that the sizing agent can effectively introduce more hydrophilic groups into the surface of the UHMWPE fibers, promote the adhesion and absorption of the fibers in the filaments to the sizing agent, and thus better improve the performance of the composite material; the interfacial shear strength and interfacial bonding strength of the modified filaments are significantly improved, proving that the adhesion and binding force of the modified sizing agent on the UHMWPE filaments are enhanced; the various data of Examples 1 and 4 are improved compared with Comparative Examples 1 and 2, and in terms of chemical structure, the adhesive A has more hard segments and fewer soft segments, and the adhesive B has more soft segments and fewer hard segments, but after PDA modification, the mechanical properties, interfacial properties, and hydrophilic properties of the UHMWPE filaments are improved, and it can be judged that the modification method of the present invention has good adaptability to the sizing agent of UHMWPE fibers. The above results show that the sizing agent prepared in Examples 1-5 has the optimized characteristics of high strength, high toughness, high adaptability, etc. after being used for UHMWPE fiber, and can be fully applied to the processing and preparation of high-strength and high-elongation materials.

[0119] Table 1

[0120]

[0121] Example 7

[0122] A method for preparing a composite material laminate comprises the following steps:

[0123] The sized UHMWPE tows prepared in the example and the comparative example were laid flat to form a unidirectional UD, and then 4 layers of unidirectional UD were cross-layered in a [0° / 90° / 0° / 90°] manner and hot-pressed and laminated in a hot press for 10 minutes to form a UD layer; then 8 UD layers were stacked and hot-pressed and laminated in a hot press for 15 minutes to form a composite material laminate.

[0124] The obtained composite material laminate was subjected to performance testing, and the test results are as follows:

[0125] Table 2

[0126] Composite laminates <![CDATA[Ballistic performance V 50 (m / s)]]> Comparative Example 1 602.53 Example 1 620.91 Example 2 601.73 Comparative Example 2 501.25 Example 3 523.29 Example 4 562.43 Example 5 592.86 Comparative Example 3 563.25 Comparative Example 4 590.23 Comparative Example 5 605.31

[0127] It can be seen from Table 2 that the ballistic performance of the composite laminates made from the tows treated with the sizing agent prepared in Examples 1-5 is significantly better than that of the corresponding unmodified adhesives. 50 The values ​​generally increase, and the impact resistance of the laminate is improved.

[0128] Comparative Example 6

[0129] A method for preparing sized UHMWPE tow comprises the following steps:

[0130] The UHMWPE tow is immersed in a dopamine hydrochloride solution (the mass ratio of dopamine hydrochloride to tris(hydroxymethyl)aminomethane hydrochloride is 0.2:0.12), and then taken out;

[0131] Adhesive A was used to perform padding and sizing on the impregnated UHMWPE tow at room temperature and pressure, with two dips and two rolls, and the roll-over rate was 65%; the tow was dried in an oven at 60° C. for 30 minutes to obtain the sized UHMWPE tow.

[0132] The results showed that the color of the tow was too dark and the dopamine polymerization was uneven.

[0133] Comparative Example 7

[0134] A method for preparing sized UHMWPE tow comprises the following steps:

[0135] Adhesive A was used to perform padding and sizing of UHMWPE tow at room temperature and pressure, with two dips and two rolls, and the roll-over rate was 65%; the tow was dried in an oven at 60°C for 30 minutes to obtain the sized UHMWPE tow;

[0136] The sized UHMWPE tow was placed in a dopamine hydrochloride solution (the mass ratio of dopamine hydrochloride to tris(hydroxymethyl)aminomethane hydrochloride was 0.2:0.12) and then taken out.

[0137] The results showed that dopamine hydrochloride could not be located on the surface of UHMWPE tow after sizing.

[0138] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A sizing agent for bulletproof material, characterized in that: The components include adhesive, dopamine hydrochloride and tris(hydroxymethyl)aminomethane hydrochloride); wherein the mass ratio of the adhesive, dopamine hydrochloride and tris(hydroxymethyl)aminomethane hydrochloride is 99.36-99.68: 0.2-0.4: 0.12-0.

24.

2. The sizing agent for bulletproof material according to claim 1, characterized in that The adhesive is a water-based polyurethane adhesive.

3. A method for preparing a sizing agent for bulletproof material according to claim 1 or 2, characterized in that: The steps include: The adhesive, dopamine hydrochloride and tris(hydroxymethyl)aminomethane hydrochloride) are uniformly mixed in a mass ratio of 99.36-99.68:0.2-0.4:0.12-0.24, and reacted to form a mixed solution; after the reaction, the mixed solution is defoamed, filtered and packaged to obtain a sizing agent for bulletproof materials.

4. The method according to claim 3, characterized in that The reaction is carried out at normal temperature and pressure with stirring at 220-300 rpm for 23-25 ​​hours.

5. A UHMWPE fiber for bulletproof material, characterized in that: The sizing agent for bullet-proof material according to claim 1 or 2 is used.

6. A method for sizing UHMWPE fibers using the sizing agent for bulletproof materials according to claim 1 or 2, characterized in that: The steps include: The UHMWPE fiber is placed in a sizing agent for bulletproof material, impregnated and rolled, and dried to obtain the UHMWPE fiber for bulletproof material.

7. A UHMWPE fiber composite material, characterized in that: The sizing agent for bullet-proof material according to claim 1 or 2 or the UHMWPE fiber for bullet-proof material according to claim 5 is used.

8. Use of the sizing agent for bullet-proof material according to claim 1 or 2, and the UHMWPE fiber for bullet-proof material according to claim 5 in the field of protective equipment or functional materials.

9. A method for improving the interfacial compatibility between resin and UHMWPE fiber, characterized in that: The sizing agent for bullet-proof material according to claim 1 or 2 is used.

10. A method for improving the tensile properties of UHMWPE fibers, characterized in that: The sizing agent for bullet-proof material according to claim 1 or 2 is used.

Citation Information

Patent Citations

  • Preparation method of modified water-based polyurethane coating

    CN107828328A

  • Method for improving interface bonding strength of fiber reinforced thermoplastic composite material

    CN113583267A

  • Ultra-high molecular weight polyethylene fiber sizing agent for polyurethane resin and preparation method of ultra-high molecular weight polyethylene fiber sizing agent

    CN116427176A

  • UHMWPE fiber and fabric surface modification and electromagnetic shielding functionalization method

    CN116575229A

  • Self-emulsifying polyurethane resin sizing agent for carbon fibers

    CN116641237A

Cited By

  • Modification method for coating tannic acid and polyether amine on surface of carbon fiber, product and application

    CN119859917A